PESANTREN TRANSFORMED IN THE AGE OF SOCIETY 5.0: DEVELOPING MULTICULTURAL-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING - Fuady, Ahmad Silmul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Pesantren is a traditional Islamic educational institution in Indonesia that has made significant contributions to the field of education. However, in the era of Society 5.0, Islamic boarding schools face challenges that require the development of more adaptive and inclusive learning methods. One such method is multicultural-based Islamic religious education. This research aims to analyze how pesantren has been transformed to meet the demands of Society 5.0 and how it has developed multicultural-based Islamic religious education as a learning method. The results show that the pesantren has undergone changes in various aspects, including its learning methods. Pesantren has started to incorporate multicultural-based Islamic religious education to face these challenges. This type of education can help students understand the universal values of Islam and the local cultural values of the surrounding community, increasing tolerance and strengthening their Islamic identity. However, there are still challenges to developing these learning methods, such as a lack of resources and awareness of the importance of multicultural education. The research aims to contribute to the development of multicultural-based Islamic religious education in pesantren , strengthening its role in Society 5.0 and creating a more inclusive educational institution.